Andean Ancient Grains: Nutritional Value and Novel Uses - Ritva Repo‐Carrasco‐Valencia; Jaime Basilio‐Atencio; Genny Isabel Luna-Mercado; Silvia Pilco-Quesada; Julio Vidaurre‐Ruiz (My University, 2022)
Quinoa, kañiwa, kiwicha and tarwi are ancient native crops from the Andes highlands of South America. Due to their remarkably high nutritional value, they offer major promise as ingredients in various food products. The aims of this study were to determine the nutritional value of certain varieties of quinoa, kañiwa, kiwicha and tarwi and to use these grains to develop novel, nutritious prototypes of products such as a malted beverage, extruded porridge, gluten-free bread and culinary dishes. The proximate, mineral and phenolic compound contents were evaluated in the Andean grains and final products. Two gluten-free breads were prepared, one made with quinoa and another made with kañiwa. An instant porridge prototype for child nutrition was developed. It had a protein content of 16% and it could, therefore, be considered to be a source of protein. The protein had a high in vitro digestibility (96.3%) and the chemical score was 0.92. The malted beverage prepared with quinoa and kiwicha had a protein content of 7.7%, which represents a value of 1.5 to 2 times more protein than dairy milk. The quinoa-amaranth beverage developed in this study is an excellent locally grown alternative to commercially available plant-based beverages usually made with soy, almond or oat, all of which are imported into Peru. Quinoa, kañiwa, kiwicha and tarwi are innovative, nutritious and tasty alternatives for restaurants seeking new ingredients for their recipes.
Keywords: Amaranth; Food science; Gluten free; Gluten; High protein; Biology; Amaranth; Food science; Gluten free; Gluten; High protein; Biology; Life Sciences Agricultural and Biological Sciences Food Science Seed and Plant Biochemistry; Life Sciences Agricultural and Biological Sciences Food Science Agricultural and Food Production Studies; Health Sciences Medicine Public Health, Environmental and Occupational Health Consumer Attitudes and Food Labeling